Respuesta :

Answer:

Step-by-step explanation:

Discussion

The object of this is make w by itself on one side of the equation.

Equation

x = 3 (y + w) - 1               Add 1 to both sides of the equation.

x + 1 = 3(y + w) - 1 + 1      Combine

x + 1 = 3(y + w)                 Remove the Brackets

x + 1 = 3y + 3w                 Notice y and w are affected by the 3. Subtract 3y

x + 1 - 3y = 3y-3y + 3w   Combine

x + 1  = 3w                       Divide both sides by 3

(x +1)/3 = 3w/3  

(x + 1)/3 = w

Answer: (x + 1)/3 = w

ACCESS MORE